A rapid microwave synthesis of green-emissive carbon dots with solid-state fluorescence and pH-sensitive properties - Yu, Tingting (R Soc Open Sci, 2018)
The emerging carbon quantum dots (CQDs) have been attracting significant attention for their prominent fluorescence, excellent stability and outstanding biocompatibility. Here, we report a facile one-step synthesis of highly fluorescent CQDs by using phthalic acid and triethylenediamine hexahydrate as precursors through a simple microwave-assisted method. The reaction time needed is only 60 s, which is less time-consuming than most previous reports. The phthalic acid with a benzene ring can improve the photoluminescence properties of CQDs as it can provide foreign sp(2) conjugating units, and then finally result in long-wavelength emission. The synthesized CQDs were fully characterized by transmission electron microscopy, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Besides, the impacts of different freed ratio on physical and chemical properties of CQDs were investigated in detail. The prepared CQDs exhibited strong green fluorescence with a broad maximum emission wavelength. The quantum yields of the CQDs can reach 16.1% in aqueous solution and they were successfully used in cell imaging with good biocompatibility. Moreover, in solid state, the CQDs with the feed ratio of 1 : 0.5 showed a strong green–yellow fluorescence which may have great potential to fabricate optoelectronic devices. Furthermore, the prepared CQDs also showed high pH sensitivity and can act as a fluorescence nanosensor for pH sensing.